Giải pt
`b) (3x^2 + 10x – 8)^2 = (5x^2 – 2x + 10)^2 `
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(2x-5\right)^2-\left(x+2\right)^2=0\)
\(\Leftrightarrow\left(2x-5+x+2\right)\left(2x-5-x-2\right)=0\)
\(\Leftrightarrow\left(3x-3\right)\left(x-7\right)=0\)
b) Cách làm giống câu a
\(\left(3x^2+10x-8\right)^2=\left(5x^2-2x+10\right)^2\)
\(\Leftrightarrow\orbr{\begin{cases}3x^2+10x-8=5x^2-2x+10\\3x^2+10x-8=-5x^2+2x-10\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}2x^2-12x+18=0\\8x^2+8x+2=0\end{cases}}\)
\(TH1:2x^2-12x+18=0\)
\(\Leftrightarrow x^2-6x+9=0\)
\(\Leftrightarrow\left(x-3\right)^2=0\Leftrightarrow x=3\)
\(TH2:8x^2+8x+2=0\)
\(\Leftrightarrow4x^2+4x+1=0\)
\(\Leftrightarrow\left(2x+1\right)^2=0\)
\(\Leftrightarrow x=\frac{-1}{2}\)
TH1: 5x2 - 2x + 10 = 3x2 + 10x - 8
=> 2x2 - 12x + 18 = 0
=> x2 - 6x + 9 = 0
=> (x - 3)2 = 0
=> x = 3
TH2: 5x2 - 2x + 10 = - 3x2 - 10x + 8
=> 8x2 + 8x + 2 = 0
=> 4x2 + 4x + 1 = 0
=> (2x + 1)2 = 0
=> x = -1/2
Vậy x = 3 , x = -1/2
b: \(\Leftrightarrow\left[{}\begin{matrix}x^2-x-2=x^2+2x\\x^2-x-2=-x^2-2x\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}-3x-2=0\\2x^2+x-2=0\end{matrix}\right.\)
hay \(x\in\left\{-\dfrac{2}{3};\dfrac{-1+\sqrt{17}}{4};\dfrac{-1-\sqrt{17}}{4}\right\}\)
c: \(\Leftrightarrow\left[{}\begin{matrix}3x^2+10x+21=x^2-20x-9\\3x^2+10x+21=-x^2+20x+9\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}2x^2+30x+30=0\\4x^2-10x+12=0\end{matrix}\right.\Leftrightarrow x\in\left\{\dfrac{-15+\sqrt{165}}{2};\dfrac{-15-\sqrt{165}}{2}\right\}\)
`(3x^2+10x-8)=(5x^2-2x+10)^2`
`<=>(3x^2+10x-8+5x^2-2x+10)(3x^2+10x-8-5x^2+2x-10)=0`
`<=> (8x^2+8x+2)(-2x^2+12x-18)=0`
\(\Leftrightarrow\left[{}\begin{matrix}8x^2+8x+2=0\\-2x^2+12x-18=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{1}{2}\\x=3\end{matrix}\right.\)
Vậy `S={-1/2 ; 3}`.
=>( 2x2 -12x +18 ) ( 8x2 +8x +2) =0
=> x2 - 6x + 9 =0 => x =3
hoặc 4x2 +4x +1 =0 =>x =-1/2
\(\Leftrightarrow\left(5x^2-2x+10-3x^2-10x+8\right)\left(5x^2-2x+10+3x^2+10x-8\right)=0\)
\(\Leftrightarrow\left(2x^2-12x+18\right)\left(8x^2+8x+2\right)=0\)
\(\Leftrightarrow\left(2x+1\right)^2=0\)
hay x=-1/2
\(PT\Leftrightarrow\left(3x^2+10x-8\right)^2-\left(5x^2-2x+10\right)^2=0\)
\(\Leftrightarrow\left(3x^2+10x-8-5x^2+2x-10\right)\left(3x^2+10x-8+5x^2-2x+10\right)=0\)
\(\Leftrightarrow\left(-2x^2+12x-18\right)\left(8x^2+8x+2\right)=0\)
\(\Leftrightarrow-4\left(x-3\right)^2\left(2x+1\right)^2=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\left(x-3\right)^2=0\\\left(2x+1\right)^2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{1}{2}\end{matrix}\right.\)
Vậy: \(S=\left\{3;-\dfrac{1}{2}\right\}\)